2014
DOI: 10.1107/s2052252514009907
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature catalyst activator: mechanism of dense carbon nanotube forest growth studied using synchrotron radiation

Abstract: The mechanism of the one-order-of-magnitude increase in the density of vertically aligned carbon nanotubes (CNTs) achieved by a recently developed thermal chemical vapor deposition process was studied using synchrotron radiation spectroscopic techniques. In the developed process, a Ti film is used as the underlayer for an Fe catalyst film. A characteristic point of this process is that C 2 H 2 feeding for the catalyst starts at a low temperature of 450 C, whereas conventional feeding temperatures are $ 800 C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There is a report showing that Fe catalyst deoxidization starts at 450 °C. 21) At the growth temperature range of 450 to 700 °C, the catalyst activation is low, and over 700 °C, the catalyst activation markedly increases in this temperature rage. There are many parameters; thus, we need to study this result further.…”
Section: Discussionmentioning
confidence: 98%
“…There is a report showing that Fe catalyst deoxidization starts at 450 °C. 21) At the growth temperature range of 450 to 700 °C, the catalyst activation is low, and over 700 °C, the catalyst activation markedly increases in this temperature rage. There are many parameters; thus, we need to study this result further.…”
Section: Discussionmentioning
confidence: 98%
“…Because of this, only the group IV metals can act as reducing agents to prevent the iron catalysts from being oxidized in the present CNT growing process. In conventional CNT growth processes with iron sputtering, several researchers [29,30] have reported that a titanium interlayer can behave as a support for the formation of iron nanoparticles, which are susceptible to oxidation but are required for dense CNT growth. Therefore, the group IV metal oxide films on the as-received substrates can support the catalytic activity of iron nanoparticles in the CVD process, as well as the alumina film developed by grit blasting.…”
Section: Effect Of Thermal Oxide Films Grown On Substrates On the Cnt...mentioning
confidence: 99%